Simultaneous Observations of EIP, TGF, Elve, and Optical Lightning. Issue 11 (28th May 2021) - Østgaard, N.; Cummer, S. A.; Mezentsev, A.; Luque, A.; Dwyer, J.; Neubert, T.; Reglero, V.; Marisaldi, M.; Kochkin, P.; Sarria, D.; Lehtinen, N.; Ullaland, K.; et al.
Abstract: On February 8, 2019, the Atmosphere‐Space Interaction Monitor observed a terrestrial gamma‐ray flash (TGF) and an Elve from a positive intracloud (+IC) lightning during the initial breakdown stage of a lightning flash north east of Puerto Rico. A second Elve produced by the return stroke (RS) of a negative cloud‐to‐ground (−CG) lightning was observed 456 ms later about 300 km south of the first one. Radio measurements show that a short (30 μs) and large (280 kA km) energetic in‐cloud pulse (EIP) produced the electromagnetic (EM) wave for the first Elve while the RS of the −CG was the EM source for the second Elve. Assuming that the EIP and the RS were the sources of the 777 nm emissions, both the delay relative to the ultra‐violet pulse and the shape and duration of the 777 nm emissions can be explained by scattering and absorption inside the clouds. The TGF produced by the +IC lightning had the same duration as the EIP (∼30 μs). Due to the ±80 μs timing uncertainty of the TGF, we can only state that TGF was produced just before or most likely simultaneously with the EIP. The large 777 nm pulse indicates that a large part of the EIP was produced by a current flowing in a hot channel, but it is likely that the TGF current also contributed significantly to the EIP. Key Points: An Elve and a TGF were produced during the vertical leader propagation in the initial phase of a positive intracloud lightning A short and strong current observed as an energetic in‐cloud pulse (EIP) produced both the EMP for the Elve and the large optical pulses The EIP was likely produced by a combination of a current in a hot leader and the TGF current